Non-thermal Influence of A Weak Microwave on Nerve Fiber Activity - Shneider, M. N.; Pekker, M. (My University, 2014)
This paper presents a short selective review of the non-thermal weak microwave field impact on a nerve fiber. The published results of recent experiments are reviewed and analyzed. The theory of the authors is presented, according to which there are strongly pronounced resonances in the range of about 30-300 GHz associated with the excitation of ultrasonic vibrations in the membrane as a result of interactions with the microwave radiation. These forced vibrations create acoustic pressure, which may lead to the redistribution of the protein transmembrane channels, thus changing the threshold of the action potential excitation in the axons of the neural network. Тhe problem of surface charge on the bilayer lipid membrane of the nerve fiber is discussed. Various experiments for observing the considered effects are also discussed.
Keywords: Microwave; E-coli C600; Cell membranes; Protein transmembrane channels